Vaginal Discharge Caused by Trichomonas Vaginalis and Candida Albicans- A Prospective Study - Begum, Syeda Humaira (The Insight, 2022)
Objective: In this study our main goal was to evaluate the cases of vaginal discharge due to Trichomonasvaginalis and Candidaalbicans. Method: This prospective analytical study was carried out in OPD of Tribhuvan University Teaching Hospital (446 bedded tertiary level hospital) from 22.05.03 to l0.10.03 between 9am to 12 noon and from 2pm to 4pm. Result: During the study, among the cases with copious vaginal discharge, 36(18.3%) patients had Trichomonasvaginalis infection and 36(18.3%) patients had Candida albicans infection i.e. total of 72 cases. Rest of 125(63.4%) cases with copious discharge did not have any infection with either T.vaginalis or C.albicans. T. vaginalis was present in 36(81.8%) cases who presented with white vaginal discharge , and Yellow/yellowish green vaginal discharge was present in 8(18.2%) cases of T. vaginalis.C.albicans was present in 40(88.9%) cases who presented with white vaginal discharge. andYellow/yellowish green vaginal discharge was present in 5(11.1%) cases of C. albicans. A total of 33(11.0%) cases had a history of taking OCP and 267(89%) cases did not have a history of taking OCP. Conclusion: It is concluded that, just a mere complaint of vaginal discharge does not really mean an infection with Trichomonasvaginalis and/or Candida albicans; moreover mixed infection with both organisms being only 2 in this study, symptomatic approach in the management of vaginal discharge does not seem to be justifiable. OCP and sexual intercourse was also found to increase the risk of Candida albicans and Trichomonasvaginalis respectively.